Study of Renal Functions in Chronic Liver Disease Patients Admitted to a Tertiary Care Hospital, Mysuru - Dr. Manoj S.B.; Dr. Deepak Raj D.; Dr. Dhanush Ray B.N., (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Background: Chronic liver disease is a major cause of morbidity and mortality worldwide, with renal dysfunction being one of its most serious complications. Hemodynamic alterations associated with portal hypertension and systemic vasodilation predispose patients to impaired renal perfusion, leading to acute kidney injury and hepatorenal syndrome. Early identification of renal dysfunction is essential to improve clinical outcomes. This study evaluated renal function abnormalities and their association with different etiologies of CLD (Chronic Liver Disease). Methods: A hospital-based cross-sectional observational study was conducted at K.R. Hospital, MMC&RI, Mysuru, from April 2023 to April 2024. Adult patients (>18 years) diagnosed with chronic liver disease were enrolled. Patients with pre-existing kidney disease, diabetes mellitus, hypertension, or a history of nephrotoxic drug use were excluded. Clinical details and laboratory parameters were collected to assess renal function and determine the incidence of renal impairment across various etiologies of CLD. Results: Among patients with chronic liver disease, renal impairment was observed in 26% of cases. The majority of affected patients were middle-aged males with alcohol-related cirrhosis. Renal dysfunction was predominantly functional in nature and attributed to portal hypertension and systemic circulatory disturbances. Serum creatinine demonstrated limitations as a reliable marker of renal function in cirrhotic patients, emphasizing the need for careful clinical evaluation and early recognition of renal impairment. Conclusion: Renal dysfunction is a common and clinically significant complication of chronic liver disease, particularly in patients with alcohol-related cirrhosis. Early detection and timely management are crucial to reducing morbidity and improving patient outcomes. The study highlights the need for improved diagnostic strategies and further research to enhance the assessment and management of renal dysfunction in chronic liver disease.